Kepemimpinan Strategis Dalam Menciptakan Organisasi Belajar Dan Organisasi Etis - Ahmad Musyarofi; Syifaus Salwa; Ulfa Nur Fajariya; Hesti Kusumaningrum (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Strategic leadership aims to create organizational learning and ethical behavior through three main activities: setting direction, designing the organization, and maintaining a culture committed to excellence and ethical conduct. Strategic leaders face challenges in overcoming resistance to change while ensuring the sustainability of decisions and addressing obstacles through the use of power. A strategic approach to developing competencies and creating a learning organization involves steps such as inspiring, motivating, empowering employees, as well as gathering and sharing internal and external knowledge. The establishment of an ethical organization includes understanding individual ethics versus organizational ethics, an integrity-based approach over mere compliance, and implementing creeds, corporate codes of ethics, and reward systems supporting ethical behavior. The conclusion of this research is that strategic leadership, involving emotional intelligence, competency development, and ethical values, can guide organizations toward sustainable excellence.excellence.